Jack of Fables. [5], Turning pages - Willingham, Bill (DC Comics, 2009)
"Jack of Fables has been around for a mighty long time, and he'll talk your ear off about his adventures if you give him half a chance. One particular episode, however, he probably won't mention. It happened back in the momentous year of 1883, and involved guns, posses, and a tangle with one Bigby Wolf. Luckily the whole story is now available here, in glorious full color, with none of the bloody or salacious details omitted. What could be better? Well, how about some in-depth history on the hottest trio of librarians since Cleopatra got a summer job in Alexandria-- not to mention the possible destruction of the entire Fable race? Do we have your attention now?" -- p. [4] of cover.